Increasing Consumer Purchasing Decisions: A Look At The Utilization Of Social Media Marketing And Servicescape At Ming Kopi - Sri Rezeki; Elisabeth Nainggolan; Nicholas Leonardi (UNIVED Press, 2025)
This study aims to analyze the effect of social media marketing and servicescape on consumer purchasing decisions at Ming Kopi, Medan City. The method used is multiple linear regression analysis with data collection through questionnaires distributed to 130 respondents. The results showed that partially, social media marketing and servicescape have a significant effect on purchasing decisions. Simultaneously, these two variables also have a significant influence on consumer purchasing decisions at Ming Kopi. This research provides insight into the importance of social media utilization and coffee shop design in increasing consumer attractiveness and purchasing decisions